2008
DOI: 10.1212/01.wnl.0000310416.90757.85
|View full text |Cite
|
Sign up to set email alerts
|

Effects of subthalamic nucleus stimulation and levodopa on freezing of gait in Parkinson disease

Abstract: Overall, subthalamic nucleus stimulation improved levodopa-responsive freezing of gait in most patients, although it was not always as effective as levodopa to improve gait impairments. In addition, surgery can induce gait problems in some patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 112 publications
(76 citation statements)
references
References 31 publications
3
69
1
3
Order By: Relevance
“…Also, it has been shown that STN stimulation can lead to gait worsening in some patients. Such an effect has mostly been reported after several years of STN stimulation [6] if not directly resulting from electrode misplacement. We controlled for such unwanted effect by checking electrode placement on the postoperative MRI and by verifying that the on stimulation scores were lower than the off stimulation scores on the objective gait item of the UPDRS III.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Also, it has been shown that STN stimulation can lead to gait worsening in some patients. Such an effect has mostly been reported after several years of STN stimulation [6] if not directly resulting from electrode misplacement. We controlled for such unwanted effect by checking electrode placement on the postoperative MRI and by verifying that the on stimulation scores were lower than the off stimulation scores on the objective gait item of the UPDRS III.…”
Section: Discussionmentioning
confidence: 97%
“…Advanced stages of PD are dominated by axial symptoms including L-FOG [6] and postural instability, as well as executive dysfunction. In addition, gait difficulties have sometimes been reported after subthalamic nucleus (STN) surgery in patients with PD [6]. …”
Section: Introductionmentioning
confidence: 99%
“…34 In contrast, other studies suggest a lesser efficacy of STN stimulation relative to L-dopa. 34, 40 Stolze et al 34 found that the improvement in stride length induced by STN stimulation was less marked than that induced by L-dopa. In addition, in a study involving a large consecutive series of patients with PD, Ferraye et al 40 analyzed a composite gait subscore (sum of items 13 ''walking'' and 14 ''freezing'' of the UPDRS Part II, and item 29 ''gait of the UPDRS Part III), the ability of the patients to perform the Stand Walk Sit Test and the frequency of FOG episodes before and after STN surgery.…”
Section: Comparison Of Levodopa and Stn Stimulation Effects On Gaitmentioning
confidence: 99%
“…34, 40 Stolze et al 34 found that the improvement in stride length induced by STN stimulation was less marked than that induced by L-dopa. In addition, in a study involving a large consecutive series of patients with PD, Ferraye et al 40 analyzed a composite gait subscore (sum of items 13 ''walking'' and 14 ''freezing'' of the UPDRS Part II, and item 29 ''gait of the UPDRS Part III), the ability of the patients to perform the Stand Walk Sit Test and the frequency of FOG episodes before and after STN surgery. Results showed that although most L-dopa-responsive gait impairments were well controlled either by L-dopa or by stimulation, in some cases there was a failure of stimulation to replicate the L-dopa-induced improvement.…”
Section: Comparison Of Levodopa and Stn Stimulation Effects On Gaitmentioning
confidence: 99%
See 1 more Smart Citation